PENINGKATAN PENGETAHUAN DAN KETERAMPILAN MENULIS CERITA FANTASI SISWA MTs MELALUI PENDEKATAN INDUKTIF - Suhud Aryana (STKIP Siliwangi, 2020)
This research is a quasi-experimental research which aims to examine the knowledge and skills of writing fantasy stories between MTs students who use the Inductive approach with ordinary learning. Researchers accept the condition of the subject as it is. In instrument trial calculations and data processing using Microsoft Excel and SPSS 24 programs. The results showed: (1) The knowledge ability of writing fantasy stories of MTs students whose learning uses an inductive approach is better than those using ordinary learning with an average of 66.98 (experimental class) and 51.40 (control class); (2) The ability of MTs students to write fantasy stories whose learning uses the inductive approach is better than those who use ordinary learning with an average of 74.30 (experimental class) and 53.60 (control class); (3) There is a very strong association between knowledge skills and fantasy story writing skills with a Q value of 0.80; (4) The difficulties experienced by students in completing questions and practical assignments in writing fantasy story texts were generally in the indicators of improving fantasy stories in terms of diction, dialogue sentences, and punctuation errors.